The adventure of the solitary cyclist - Doyle, Arthur Conan, Sir, 1859-1930. (Mankato, MN : Creative Education, 1991)
Miss Violet Smith asks the great Sherlock Holmes to investigate the mysterious bearded man who is following her on a bicycle.
Keywords: Mystery and detective stories